ECONOMIC AND SOCIAL DIMENSIONS OF AGRI-FOOD SECTOR IN THE SLOVAK REPUBLIC - Maroš VALACH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the paper is to analyse selected economic and social aspects of the agri-food sector in the Slovak Republic. The source of data was the Statistical Office of the Slovak Republic as well as the National Agricultural and Food Centre Branch: Research Institute of Agriculture and Food Economics. A typical feature of Slovakia is that its territory is mainly dominated by rural areas, of which agriculture is an integral part, fulfilling not only an economic but also a social role. According to the latest Structural Farm Survey, there are 25658 farms in Slovakia, owned by legal and natural persons, which manage 1,889,819 ha of utilised agricultural land. The largest group is made up of registered and unregistered natural persons (87.8 %) and the smallest group is made up of legal persons (12.2 %). The situation is reversed in terms of the size of the land farmed, with legal persons farming 80.0 % of the agricultural land and natural persons farming only about 20 %. The number of persons employed in agriculture is 46.46 thousand and the remuneration of employees is lower than in other sectors of the national economy. In terms of status, employees account for 87.4% and entrepreneurs 12.6%.